THE IMPORTANCE OF MUMIYO IN THE TREATMENT OF BROKEN BONES (Лучшие интеллектуальные исследования, 2025)
Annotation: The article presents literature data on the use of the drug Mumiyo in the treatment of bone fractures, as well as the results of numerous experimental studies conducted by scientists around the world and in our country on the effect of Mumiyo in bone fractures on reparative regeneration of bone tissue, blood biochemical parameters and mineral metabolism.Аннотация: В статье представлены литературные данные о применении препарата мумие при лечении переломов костей, а также результаты многочисленных экспериментальных исследований, проведенных учеными мира и нашей страны по влиянию мумие при переломах костей на репаративную регенерацию костной ткани, биохимические показатели крови и минеральный обмен